2014
DOI: 10.1037/a0035321
|View full text |Cite
|
Sign up to set email alerts
|

Workplace discrimination predicting racial/ethnic socialization across African American, Latino, and Chinese families.

Abstract: Informed by Kohn and Schooler's (1969) occupational socialization framework, this study examined linkages between racial/ethnic minority mothers' perceptions of racial/ethnic discrimination in the workplace and adolescents' accounts of racial/ethnic socialization in the home. Data were collected from 100 mother-early adolescent dyads who participated in a longitudinal study of urban adolescents' development in the Northeastern United States, including African American, Latino, and Chinese families. Mothers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 34 publications
3
51
3
Order By: Relevance
“…Research has indicated that African American mothers' workplace experiences are significantly different from those of other racial groups (Buzzanell, Waymer, Paz Tagle, & Liu, ; Hagelskamp & Hughes, ; Landivar, ). African American mothers do not scale back when they have children but often work additional hours because of single parenthood or lower family income (Buzzanell et al, ).…”
Section: African American Mothers and Academiamentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that African American mothers' workplace experiences are significantly different from those of other racial groups (Buzzanell, Waymer, Paz Tagle, & Liu, ; Hagelskamp & Hughes, ; Landivar, ). African American mothers do not scale back when they have children but often work additional hours because of single parenthood or lower family income (Buzzanell et al, ).…”
Section: African American Mothers and Academiamentioning
confidence: 99%
“…Paz Tagle, & Liu, 2007;Hagelskamp & Hughes, 2014;Landivar, 2013). African American mothers do not scale back when they have children but often work additional hours because of single parenthood or lower family income (Buzzanell et al, 2007).…”
mentioning
confidence: 99%
“…Still other authors have observed null effects. Hagelskamp and Hughes (2014) collected data from working mothers and did not find any differences in racism experienced at work, while Barron et al (2011) observed that people responded similarly to Irish, Hispanic and African American job applicants who seemingly expressed a strong ethnic identity. These ostensibly equivocal results suggest there is need for additional inquiry, and that perhaps other factors, such as those described in the subsequent sections, influence the relationship between racial group membership and discrimination.…”
Section: Moderatorsmentioning
confidence: 99%
“…As previously noted, recent work on race and race relations points to the need for considering the potentially varying experiences and expectations of different racial minority groups (Richeson and Sommers, 2016). While the limited experimental work in this area offers equivocal results (Barron et al, 2011;Fox and Stallworth, 2005;Hagelskamp and Hughes, 2014), nationally representative data from the Pew Research Center and the US Bureau of Labor Statistics suggest Latinas, relative to African American women, are more likely to experience discrimination and to earn less (Hispanics, 2010). As such, we predicted that:…”
Section: Study Overview and Hypothesesmentioning
confidence: 99%
“…In the work environment, discrimination usually occurs when the actions of an employer, supervisor, or co-worker deny individuals or groups of people the equality of treatment they may wish [14]. The workplace provides opportunities for stereotyping, prejudice, and discrimination [15], in particular if it is systemic race-based discrimination [16].…”
Section: Introductionmentioning
confidence: 99%